Determinación de la presencia de Virus de Inmunodeficiencia Felina en gatos de La Ciudadela Barrio Lindo de la ciudad de Babahoyo - Martínez Yance, Kevin Nelson (2023)
Feline immunodeficiency virus is a pathology that affects strictly cats. This is because most cats in our surroundings live on the streets without any control or sterilization. Considering that there is still no specific vaccine against this pathology, the only way to prevent it is by sterilizing your cat. This helps reduce the production of both male and female sexual hormones, preventing mating, fights, violations, etc. For this reason, I conducted a study on 30 felines (cats) using different rapid tests in the neighborhood of Barrio Lindo in the city of Babahoyo, in the province of Los Ríos. The objective was to determine the presence of the feline immunodeficiency virus (FIV) using chromatography immunoassay tests to detect the FIV antigen. It was discovered that 20% (6 cats) of the studied felines tested positive for FIV, while 80% (24 cats) tested negative. Most of the studied felines were between 1 to 3 years old, and almost all of them were not sterilized, thus leading an autonomous life and being at risk of contracting various diseases, including FIV, as they were not up to date with their vaccination schedule. Proper care and feline sterilization are recommended to prevent FIV contagion, as this virus is transmitted through bites, scratches, and mating. To maintain a proper schedule, it is recommended to perform FIV immunochromatography tests every three months.